Documentation On Medicinal Plants of Khanapur Forest Bidar District, Karnataka - Siddharth Kanche,; Dr. Vaishali Sidram Chatage, (International Journal of Scientific Research in Science and Technology, 2024)
The present study was undertaken to document medicinal plants of Khanapur forest Bidar district, karnataka the documentation of medicinal plants helps to recognize the overall ecological conditions and gives profound understanding of the economic medicinal and traditional importance of medicinal plants diversity. The present research documentation work was started in November 2023 and completed in February 2024. The present study reported that 119 Medicinal plant species belongs to 54 families distributed in Khanapur forest Bidar included angiosperms Pteridophytes and Gymnosperms. Abrus precatorius, Ephedra, Withania sominifera, Catharanthus roseus, Tinospora cardifolia, Andrographis paniculata, Phyllanthus amarus, allium sativum, Cocos nucifera, Coleus aromaticus, Curcuma longa, Martynia annua, Ocimum tenuiflorum, Tamarindus indica, Terminalia chebula,Tithonia diversifolia, Acalypha indica, Brassica juncea, Clitoria ternatea, Datura metal, Delonix elata, Euphorbia antiquorum, Luffa acutangula, Madhuca longifolia, Myristica fragrans, Santalum album and Vitex negundo are some of the important medicinal plants of Khanapur forest Bidar district of karnataka.
Keywords: Documentation; Khanapur Forest; Bidar; Karnataka; Medicinal Plants